RANCANG BANGUN SISTEM INFORMASI PENJUALAN SEMBAKO MENGGUNAKAN MODEL WATERFALL ( Studi Kasus : Koperasi Karyawan PT. Frisian Flags) - Syamsul Bakhri (Jurnal Khatulistiwa Informatika, 2015)
In the current era of globalization, information technology evolving so rapidly. The computer is the equipment created to facilitate the work of man. Cooperative employees rmembutuhkan once the existence of a system that can support the sales and provide better services to members. For this reason the author tried to designing information systems selling groceries on credit in the Cooperative Employees PT Frisian Flag Indonesia Plant Ciracas that until now there has been computerized and is still done manually, ranging from notes receivable, making statements to the data storage more still associated with the process of selling groceries, allowing the error occurs during the process as well as the lack of accuracy in recording the statements are made and the problem of delay in the search for the required data. This information system is the best solution to solve the problems that exist in this company. With a computerized system that can achieve an effective and efficient activities to support the activities of the company. A computerized system is better than the manual system so that existing activities in a company/agency to operate more effectively and efficiently and can be more conducive compare with the previous system.Keywords: System Design Sales, Sales groceries on credit